TRAINING NEEDS OF IRRIGATED WHEAT GROWERS IN THE DISTRICT OF BAIJI _ GOVERNORATE OF SALAH ALDDIN AND ITS RELATION WITH SOME VARIABLES -2. - Ghaidhaib, Ali Ahmed; Mohammed, Dua ’A Diaa (Diyala Agricultural Sciences Journal, 2013)
This research aims at estimating the training needs of irrigated wheat farmers in all of its areas of wheat farming and detecting the relation between the training needs and all of the variables (number of years in experience, farming supplies, information sources, prior training, the openness and being ready for change) and the relation between the training needs and a group of independent factors and also examining all the problems that face irrigated wheat farmers in Baiji. Research samples have included (150) farmers standing for (15%) of all the farmers in Baiji. The data of the research were collected by a questionnaire form done specially to estimate the training needs and the first part of it includes social, economic and calling data, while the second part includes (52) paragraphs to estimate the training needs of irrigated wheat farmers. The truthfulness of the outer and the inner content has been fulfilled and it was accounted according to the half separating and the rate of standing was (0,70). After classifying data, the relation worker Person was used and the rank relation for Spearman and multi stages test for analyzing data. The results showed that the rank of irrigated wheat farming according to the need to train as follows: holocaust, fertilization, the date of farming, harvesting, diseases and insects, the way of farming, irrigation, sowing, formatting the earth. The results indicate the existing of a concrete connection relation between the training needs of irrigated wheat farmers and information sources , openness and being ready for change, whereas there is no concrete connection relation with years of experience in farming and farming supplies and prior training. The results also showed that the change of openness and being ready for change is most contributing in interpreting the variation in the level of the training needs then information sources follows. Depending on these results, some conclusions have been made and some recommendations have been suggested.